2015
DOI: 10.1093/mnras/stv2078
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy morphology and star formation in the Illustris Simulation atz = 0

Abstract: We study how optical galaxy morphology depends on mass and star formation rate (SFR) in the Illustris Simulation. To do so, we measure automated galaxy structures in 10808 simulated galaxies at z = 0 with stellar masses 10 9.7 < M * /M < 10 12.3 . We add observational realism to idealized synthetic images and measure non-parametric statistics in rest-frame optical and near-IR images from four directions. We find that Illustris creates a morphologically diverse galaxy population, occupying the observed bulge st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
195
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(222 citation statements)
references
References 135 publications
25
195
0
Order By: Relevance
“…Kauffmann et al 2003). In Snyder et al (2015b), non-parametric optical morphologies were calculated for thousands of Illustris galaxies, and they were found to be in good agreement with their observational counterpart (Lotz et al 2008). Furthermore, Genel et al (2015) found that the specific stellar angular momenta of Illustris galaxies are consistent with observational trends (Romanowsky & Fall 2012;Fall & Romanowsky 2013).…”
Section: Galaxy Morphology Revisitedsupporting
confidence: 53%
See 1 more Smart Citation
“…Kauffmann et al 2003). In Snyder et al (2015b), non-parametric optical morphologies were calculated for thousands of Illustris galaxies, and they were found to be in good agreement with their observational counterpart (Lotz et al 2008). Furthermore, Genel et al (2015) found that the specific stellar angular momenta of Illustris galaxies are consistent with observational trends (Romanowsky & Fall 2012;Fall & Romanowsky 2013).…”
Section: Galaxy Morphology Revisitedsupporting
confidence: 53%
“…In this work we explore the origin of discs and spheroids using the Illustris simulation (Vogelsberger et al 2014a,b;Genel et al 2014;Sijacki et al 2015), a hydrodynamic cosmological simulation that has been shown to reproduce several galaxy observables reasonably well, including stellar angular momenta and quantitative optical morphologies Snyder et al 2015b), over a wide range of stellar masses. This makes the Illustris simulation a powerful tool to study the physical mechanisms that shape galaxy morphology in a cosmological context.…”
Section: Introductionmentioning
confidence: 99%
“…Such an analysis has been done for the Illustris numerical hydrodynamical simulations at z = 0, by Snyder et al (2015). The top left panel of their Figure 5 is strikingly similar to our redshift zero panel from Figure 3, although it should be kept in mind that their color coding is based on a different metric representing how bulge-dominated the galaxy is (Gini-M20).…”
Section: Comparison With Other Theoretical Studiessupporting
confidence: 52%
“…On the simulation side, Snyder et al (2015) investigated the relationship between optical morphology, stellar mass and star formation rate for a sample of simulated galaxies from the Illustris simulation (Vogelsberger et al 2014). They found that their model, which includes feedback from accreting supermassive black holes, was able to produce the population of quiescent bulge-dominated galaxies at z ∼ 0 needed to reproduce the distribution of observed morphologies.…”
mentioning
confidence: 99%
“…Initial efforts are underway to systematically mock-observe large sets of galaxies from hydrodynamical simulations (e.g., Torrey et al 2015;Snyder et al 2015b;Trayford et al 2015Trayford et al , 2016Kaviraj et al 2016). Because Illustris resolves galaxy structures on spatial scales below ∼ 1 kpc at z 1, its mock survey fields contain sources appropriate for comparing with existing deep, high resolution, but narrow survey fields.…”
Section: Discussion and Summarymentioning
confidence: 99%